2018
DOI: 10.3201/eid2408.180126
|View full text |Cite
|
Sign up to set email alerts
|

Human Norovirus Replication in Human Intestinal Enteroids as Model to Evaluate Virus Inactivation

Abstract: Human noroviruses are a leading cause of epidemic and endemic acute gastroenteritis worldwide and a leading cause of foodborne illness in the United States. Recently, human intestinal enteroids (HIEs) derived from human small intestinal tissue have been shown to support human norovirus replication. We implemented the HIE system in our laboratory and tested the effect of chlorine and alcohols on human norovirus infectivity. Successful replication was observed for 6 norovirus GII genotypes and was dependent on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
233
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(287 citation statements)
references
References 32 publications
18
233
0
1
Order By: Relevance
“…We hypothesize that a substantial proportion of asymptomatic patients are shedding infectious norovirus and that their role in spreading the virus merits our attention. We have shown that high levels of norovirus replication can be achieved from fecal samples of adults, not just young children, in HIE cultures ( 11 ). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesize that a substantial proportion of asymptomatic patients are shedding infectious norovirus and that their role in spreading the virus merits our attention. We have shown that high levels of norovirus replication can be achieved from fecal samples of adults, not just young children, in HIE cultures ( 11 ). …”
Section: Discussionmentioning
confidence: 99%
“…Second, virus culture systems in cell lines generally lack sensitivity ( 12 ), and that of HIE remains unknown. However, it is probably not optimal because input genome equivalents for norovirus to achieve replication are not extremely low (50% infectious dose 4.4 × 10 2 to 2.1 × 10 3 copies/well) ( 3 , 11 ). It is possible that samples with C t >30 might still contain infectious virus and that low amounts of replicating norovirus would only be detected with further serial propagation of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a system utilizing human intestinal enteroids (HIE) was reported to support replication of human norovirus (10). Moderate replication levels could be enhanced with addition of bile acids, however the replication success was still strongly dependent on the particular stool sample (28). This cell culture system highlighted the requirement of HBGAs on the surface of permissive cells and showed that HBGA blocking sera can effectively neutralize norovirus.…”
Section: Introductionmentioning
confidence: 99%
“…This cell culture system highlighted the requirement of HBGAs on the surface of permissive cells and showed that HBGA blocking sera can effectively neutralize norovirus. Importantly, the HIE system was used to evaluate the neutralizing properties of 25 different GII.4 specific IgG and IgA isolated from a human donor (28). Several antibodies were able to neutralize human norovirus and were predicted to bind to the P domain, however the precise binding sites were not yet determined.…”
Section: Introductionmentioning
confidence: 99%